Circulating tumor cell telomerase activity as a prognostic marker for overall survival in SWOG 0421: A phase III metastatic castration resistant prostate cancer trial. Issue 8 (8th October 2014) - Goldkorn, Amir; Ely, Benjamin; Tangen, Catherine M.; Tai, Yu‐Chong; Xu, Tong; Li, Hongli; Twardowski, Przemyslaw; Veldhuizen, Peter J. Van; Agarwal, Neeraj; Carducci, Michael A.; Monk, J. Paul; Garzotto, Mark; et al.
<x xml:space="preserve">Abstract</x> Circulating tumor cells (CTC) are promising biomarkers in metastatic castration resistant prostate cancer (mCRPC), and telomerase activity (TA) is a recognized cancer marker. Therefore, we hypothesized that CTC TA may be prognostic of overall survival (OS) in mCRPC. To test this, we used a novel Parylene‐C slot microfilter to measure live CTC TA in S0421, a phase III SWOG‐led therapeutic trial. Blood samples underwent CTC capture and TA measurement by microfilter, as well as parallel enumeration by CellSearch (Janssen/J&J). Cox regression was used to assess baseline (pre‐treatment) TA versus OS, and recursive partitioning was used to explore potential prognostic subgroups and to generate Kaplan‐Meier (KM) OS curves. Samples were obtained from 263 patients and generated 215 TA measures. In patients with baseline CTC count ≥5 (47% of patients), higher CTC TA was associated with hazard ratio 1.14 (p = 0.001) for OS after adjusting for other clinical covariates including CTC counts and serum PSA at study entry. Recursive partitioning identified new candidate risk groups with KM OS curve separation based on CTC counts and TA. Notably, in men with an intermediate range baseline CTC count (6–54 CTCs/7.5 ml), low versus high CTC TA was associated with median survival of 19 versus 12 months, respectively (p = 0.009). Baseline telomerase activity from CTCs live‐captured on a new slot microfilter is the first CTC‐derived candidate biomarker prognostic of OS in a large patient subgroup in a prospective clinical trial. CTC telomerase activity thus merits further study and validation as a step towards molecular CTC‐based precision cancer management.